UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA EKOSISTEM DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH DI SMA NEGERI 1 PALIPI SAMOSIR - Sriayu Sinaga; Binari Manurung (Universitas Negeri Medan, 2016)
This study aims to determine the improvement of activities and learning outcomes of studentby usingproblem based learning (PBL) model at topic of ecosystem in the class X-1 SMA Negeri 1 Palipi Samosir districtin Academic Year 2015/2016. This research is a classroom action research. The subject of this study was gradex-1 in the class SMA Negeri 1 Palipi Samosir the student numbers 30 people. The techniques of data analysisare by computing the percentage of student learning outcomes and learning completeness. This average valueof the pretest was 47,74. After applying outdoor study with problem based learning (PBL) model, the averagevalue of posttest I in cycle I was 70.87 and the posttest II in cycle was 82.63. This indicated there was animprovement in learning outcomes of the posttest I and posttest II for about 12. The learning completenesswhich as gained in cycle I was 16 student (53.3 %) of all the student and in cycle II it was 26 students (86.7%), sothe learning completeness was reached. For the data indicator of achievement percentage is know that in thefirst cycle of Leraning objectivesset out in the second indicator has not been achieved. While the second cycleindicator has been reached. For student learning activity data that the level of student learning activities hasindreased from 47.67% (first cycle I) to 87% (cycle).Key words: learning outcomes, activities, problem based learning models and cycle.